Pinking in White Wines - A Review - Nel, A.P.; du Toit, W.J.; van Jaarsveld, F.P. (South African Journal of Enology and Viticulture, 2020)
In the late 1960s, a phenomenon was discovered in white wines. It was noted that certain white wines turned pink in the bottle. This phenomenon was dubbed as pinking. Research was done on the pinking to establish its cause and effect. Analysis of SO2, pH and polyvinyl polypyrrolidone (PVPP) showed that a minimum of 45 mg/L of SO2 were needed for the wine not to be susceptible to pinking. Tests on the decrease in pH showed that there was no increase in pink colour with a decrease in pH, which meant that monomeric anthocyanins were not the cause of pinking. Recent research claims that malvidin-3-Oglucoside is the most abundant monomeric anthocyanin found in pinked wines and could be the cause of pinking. This led to the theory that phenols contribute to pinking susceptibility, and this was accepted as fact in recent years. The establishment of a pinking assay in 1977 made the testing for pinking easier and cheaper for winemakers. The sales of PVPP increased as winemakers worked preventatively with their wine to decrease susceptibility to pinking. This review attempts to describe the history of pinking, the establishment of the assay, as well as to describe factors that could lead to pinking susceptibility in white wines.